Analisa Hukum Pasal 66 Undang-Undang Nomor 2 Tahun 2014 Tentang Jabatan Notaris Mengenai Penyimpanan Protokol Notaris Yang Berumur 25 Tahun Oleh Notaris Penerima Protokol Kepada Majelis Pengawas Daerah Notaris - Leny Agustan (Fakultas Hukum Universitas Tamansiswa Padang, 2025)
Notaries have the authority to make authentic deeds, which are called Notarial deeds. The authenticity of Notarial Deeds remains, even until the Notary dies, which is called the Notarial Protocol. Notarial Protocols must be kept by the Notary for an unlimited period of time. Article 63 Paragraph (5) of the Notarial Position Law states that Notarial protocols from other Notaries whose submission is 25 years old or more, are submitted to the Notary Regional Supervisory Board, but the provisions of Article 63 Paragraph (5) are not implemented, the Notary Receiving the Protocol does not submit the minutes that are 25 years old to the Regional Supervisory Board and still keeps the protocol at the Notary Receiving Protocol Office. Based on this description, problems arise regarding, 1) How is the legal analysis of the storage of notarial protocols that are 25 years old by the notary receiving the protocol to the regional supervisory board? 2) How is the authority of the notary as the recipient of the protocol to issue a copy of the minutes of a deed that is more than 25 years old? Based on the formulation of the problem above, the objectives to be achieved in this study are as follows: 1) to determine the legal analysis of the storage of notary protocols that are 25 years old by the notary receiving the protocol to the regional supervisory board. 2) to determine the authority of the notary as the recipient of the protocol to issue a copy of the minutes of the deed that are more than 25 years old. This study uses a normative legal research approach. The main material of this study is Secondary Data obtained from various pre-existing data based on laws, literature and other legal studies. Primary data from primary, secondary and tertiary legal materials, using qualitative data analysis and presented in descriptive form. The results of this study indicate that the storage of Notary protocols that are 25 (twenty five) years old or more as regulated in Article 63 paragraph (5) of the Notary Law must be carried out by both the Notary Receiving the Protocol and the Notary MPD, but this is not implemented due to the lack of infrastructure owned by the Notary MPD. The Notary Receiving the Protocol has the obligation to store and maintain it, and for the purposes of a copy of the minutes of the deed, the Notary Receiving the Protocol still has the authority as long as the Notary is in office and has the right to issue a copy of the minutes (received protocol), the Notary MPD does not have the authority to issue a copy of the minutes because there is no authority granted by law to the Notary MPD.